Yuelushannus gen. nov. (Araneae, Linyphiidae) from China - Irfan, Muhammad; Zhou, Gu-chun; Bashir, Shahida; Mukhtar, Muhammad Khalid; Peng, Xian-jin (European Journal of Taxonomy, 2020)
The new erigoninae genus Yuelushannus gen. nov. with two new species, Y. alatus sp. nov. (♂♀) and Y. barbatus sp. nov. (♂♀), are described from Hunan and Hubei Provinces. Detailed descriptions of somatic features and genitalic characters, photos of the habitus and copulatory organs, line drawings of copulatory organs and a distribution map are provided.